‘There is water available and so our hearts are at peace’: exploring the impact of access to safe water on women's subjective well-being in Ghana - Prosperous Ahiabli; Peter Adatara; Ruth Cross (Journal of Water, Sanitation and Hygiene for Development, 2023)
Women from Kordorwukope and Gbegbevia had to travel about 2 km to access safe water, until 2018 when International Needs Ghana, a Non-Governmental Organisation, extended piped water to each of the two communities. Since the extension of water to the communities, no study had been carried out to ascertain the effects of access to safe water on the well-being of women living in those communities. This study therefore aimed at exploring the effects of physical access to safe water on the well-being of women living in the Gbegbevia and Kordorwukope Communities. A qualitative research design was used. The study population included seven women who had lived in the study communities for at least 2 years before the water project was implemented. Five key themes were apparent in the data: challenges women encountered before gaining access to safe water; physical well-being; mental well-being; social well-being; and career and financial well-being. The results of this study show that the extension of piped water to the study communities brought about significant improvement in physical, mental, social, career, and financial well-being of women in the study communities. HIGHLIGHTS By using a qualitative design, this article explores and gives a rich description of women's lived experiences in accessing safe water.; This article explores the impact of access to clean water on multiple dimensions of women's subjective well-being.; The article projects water as an important social determinant of health, which contributes meaningfully to holistic health as defined by the World Health Organisation.;